Enjoying "First Sale": An appreciation of lending from then to now - Turvey-Welch, Michelle; Sibley, Gwendolyn; Otto, Ryan; Kickbusch, Scott; Jackson, Carolyn; Berney, Elizabeth (My University, 2025)
Libraries have enjoyed the benefits of the first sale doctrine for over 100 years, empowering libraries to lend lawfully purchased physical materials to patrons in their communities. As the information landscape has developed, libraries have moved from lending just physical materials to digital as well. With interlibrary loan (ILL) creating a network of broader lending systems and libraries taking on the challenge of license negotiations, library lending has evolved. Libraries now create and facilitate dissemination of works through library-based publishing and open access initiatives. This presentation seeks to celebrate the ability of libraries to lend and accentuates the changes that have affected Academic Librarianship over the past 50 years. Participants will learn about law that supports libraries, how collection development has evolved, the resulting shift in interlibrary loan, and how libraries promote the research cycle through library publishing. The presenters hope to start conversations about the state of library lending and the possibility of a future where libraries no longer enjoy first sale.